Implementation Challenges of STEM Education: from Teachers’ Perspective (International Conference on Computers in Education, 2020)
How to effectively support teachers in implementing STEM education is regarded as an urging issue in school education. To address this issue, we need to gain a better understanding of teachers’ implementation challenges of STEM education. This qualitative research collected views from the teachers who participated in a STEM education training programme. After the programme, four teachers took part in the semi-structured interviews. The study revealed that their lack of (i) pedagogical content knowledge (PCK) and (ii) external support were the main challenges that they were facing. Suggestions to facilitate teachers’ STEM education implementation in schools, as well as research implications, are proposed and discussed.